Evaluation of SAFEChildren, a Family-Focused Prevention Program in Chicago, Illinois, 2006-2010 - Tolan, Patrick ([Verlag nicht ermittelbar], 2013)
Schools and Families Educating Children (SAFEChildren) is a family-focused program designed to aid families residing in high risk communities with child development during the child's transition to school. The program has the goal of building protection and impeding risk trajectories for aggression, violence, and school failure. The program utilizes multiple family groups (four to six families) combined with reading tutoring for the child. The SAFE Effectiveness Trial (SAFE-E) involved community providers delivering the family group intervention and upper grade students delivering the tutoring program. The trial took place between 2006 and 2010, and involved two age cohorts of children. Collaborating with two community mental health agencies and six elementary schools serving high-poverty, high-crime neighborhoods in Chicago, Illinois, families were randomly assigned to intervention groups of four to six families during their child's first grade year. Children also received tutoring from tutors selected from the upper grades of the child's school. Assessments were collected prior to, during and after the intervention to assess developmental influences, fidelity, process, and implementation characteristics that might affect impact. The purpose of these assessments was to examine the relation of implementation qualities to variation in intervention effects. Quality of implementation was expected to affect short and long-term impact of the intervention, focusing on three primary areas: (1) fidelity of implementation of the program, (2) provider characteristics, such as tutors' reading levels, and attitudes and orientation of the family intervention providers, and (3) quality of support for implementation. The data are from fidelity and process measures developed for this study and measures completed by parents, teachers, and children over four waves of measurement spanning two years, beginning in the fall of each child's first grade year.